Sensitivity of cotton cultivars to soil compaction - Falkoski Filho, Jorge [UNESP]; Batista, Itaynara [UNESP]; Rosolem, Ciro Antonio [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
Cotton is one of the most sensitive crops to soil compaction, but there may be genetic variability for this trait. The objective of this study was to evaluate cotton cultivars sensitivity to soil compaction. Soil columns were built with three pvc rings with internal diameter of 10 cm and filled with an alfisol. The heights of the top and bottom rings were 15 cm, and the intermediate ring, in which the soil was compacted, was 3.5 cm high. The levels of compression used in the subsurface were characterized by penetration resistances of 0.41, 0.93, 1.41 and 1.92 MPa. The cultivars 701 FMT, FMT 705, FMT 707, FMX 951 LL and FMX 966 LL were grown up to 23 days after plant emergence, when the dry matter of shoots and roots, root length density and root diameter were determined. The cotton cultivars have variability in their sensitivity to resistance to penetration. The cultivar 707 FMT is more sensitive to soil compaction, while the FMT 701 is more tolerant. Penetration resistance of around 0.92 to 1.06 MPa reduce 50% cotton root growth, but resistance to penetration of 1.92 MPa did not totally prevent growth.
Keywords: Gossypium hirsutum; penetration resistance; root growth; Q(1/2) index